A device for rapid calorimetric measurements on small biological tissue samples - Lerchner, Johannes; Hervas, Livia S. [UNESP]; Bícego, Kenia C. [UNESP]; Garcia, Geovana S. [UNESP]; Oliveira, Marcos T. [UNESP]; Hasic, Mersiha; Klingenspor, Martin; Mertens, Florian (Springer Nature, 2024)
A new calorimetric technique is described that allows high-throughput heat production rate measurements on small biological tissue samples. The technique is based on the widely used thermopile chip technology combined with an innovative method for precise transport and positioning of samples of different biological materials at the thermal power detector inside the calorimeter. The new transport and positioning technique is a combination of fluidic and mechanical transport, where the latter is realized by a magneto-motor drive. The transport facility ensures good diffusive oxygen penetration into the sample, which is essential for highly metabolically active materials. The proper functioning of the device is demonstrated by measuring the heat production of metabolically active brown adipose tissue, biopsied tegu lizard muscle, and live Drosophila larvae at different stages and temperatures.
Keywords: Biological tissues; Brown adipose tissue; Chip calorimetry; Drosophila larvae; Tegu lizard muscle tissue